Screening for obstructive sleep apnoea in patients with serious mental illness. (October 2022) - Zhang, Lai-Ying; Anderson, James; Higgins, Niall; Robinson, Jan; Francey, Sonia; Burke, Andrew; Robinson, Gail; Curtin, Deanne; Tay, George
Objective: Patients with serious mental illness (SMI) are at increased risk of obstructive sleep apnoea (OSA). Despite this, OSA is frequently under-recognised in the psychiatric population. This study describes the results of OSA screening in SMI patients. Method: Patients with SMI attending a metropolitan mental health clinic were screened for OSA using the OSA50, STOP-BANG Questionnaire (SBQ), Epworth Sleep Score (ESS) and the Pittsburgh Sleep Quality Index (PSQI). They were then offered diagnostic sleep testing via ResMed ApneaLink TM and polysomnography. Results: Of the 65 patients recruited, 65% had a primary diagnosis of schizophrenia or schizoaffective disorder, 85% were on antipsychotic medications and the majority were obese. Approximately 50% of patients reported poor sleep quality via the PSQI, in contrast to 12% with elevated daytime sleepiness via the ESS. 46% of our cohort were at risk of OSA due to an elevated OSA50 or SBQ. Of the five patients who agreed to proceed to diagnostic sleep testing, three were diagnosed with OSA. Conclusion: A high proportion of patients with psychiatric illness are at risk of sleep-disordered breathing. Sleep dissatisfaction is high. The low uptake of sleep investigation requires improved patient engagement to improve OSA diagnosis in this high-risk group.